Progress of Potato Late Blight on Staggered Planting in High Hills of Meghalaya - GURJAR, MS; BAG, TK; SURAJ SINGH, K (Indian Journal of Hill Farming, 2015)
Late blight susceptible cultivar, Kufri Jyoti was planted at three dates with 15 days interval starting from 15 February to 15 March to analyze the progress of late blight. The disease appeared in 2nd to 3rd week of May in Meghalaya high hills. Disease appeared after 72, 62 and 53 days of planting in 2011 while it appeared after 93, 78 and 52 days of planting in 2012. Progress of late blight was lower in first date of planting (AUDPC 812-882) as compared to second (AUDPC 1102.5-1162) and third dates (AUDPC 1102.5-1137.5) of planting. The highest tuber yield (33.33 t/ha) was observed in first date of planting (15 February) followed by second and third dates. It was concluded that yield reduction due to late blight can be avoided by planting in the middle of February in Meghalaya.